Transformasi Strategi Komunikasi Pemasaran Pesantren di Era Society 5.0: Studi Etnografi dan Netnografi Virtual - Mujiburrohman; Hefniy (Visionaria: Journal of Educational Innovation Management, 2025)
This study aims to analyze the transformation of the marketing communication strategy of the Nurul Jadid Islamic Boarding School in the Society 5.0 era through virtual ethnography and netnography approaches. In the context of the digitalization of Islamic education, this study highlights how the Islamic boarding school builds its image and builds rapport with the public through various social media platforms such as YouTube, Instagram, Facebook, and TikTok. Using a qualitative, descriptive case study method, data was obtained through online observations, in-depth interviews with media managers, students, and guardians, and digital content analysis. The findings indicate that the Islamic boarding school's communication strategy has undergone a significant shift from conventional methods such as print media and offline promotions to digital communication patterns based on Islamic values. The digital content created not only functions as a promotional tool but also as a means of preaching, education, and internalization of constructive and contextual Islamic values. This strategy has had a positive impact on increasing engagement, public perception, and the effectiveness of widespread and rapid information dissemination. However, the study also identified several challenges such as limited digital literacy, the content dilemma between media aesthetics and Islamic norms, and the dynamics of social media algorithms. Based on these findings, this study recommends strengthening the capacity of Islamic boarding school digital teams, developing Islamic value-based content guidelines, and collaborating with media and da'wah experts to maximize the potential of digital communication in the Islamic boarding school context. This research provides theoretical contributions to the field of Islamic marketing communications and offers an applicable strategic framework for Islamic educational institutions to navigate the digital era adaptively and effectively.